2020
DOI: 10.5109/4055238
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-based Energy Management System for Prosumer

Abstract: The rapid development of RES technology produces cheaper and compact devices. This condition has attracted the household to install the RES devices on their premises. Hence, the household has changed from the passive electricity consumer into the active prosumer. The active prosumer not only consumes the electricity but also have the capability to produce electricity. However, the electricity produced by RES devices is intermittence and unstable. Moreover, the behavior of the inhabitants of the prosumer also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The data in the database is from different sources these sources are connected through knowledge graphs 64) . So, all information from different sources will be shown on the Google Home page 65) suggesting information about the knowledge graph 66) . The next section explains the proposed framework for gathering the recent trends in the Knowledge graph research field for the number of scientific articles found in this field and the major areas/regions/countries that contributed more to this field 67) .…”
Section: Knowledge Graphmentioning
confidence: 99%
“…The data in the database is from different sources these sources are connected through knowledge graphs 64) . So, all information from different sources will be shown on the Google Home page 65) suggesting information about the knowledge graph 66) . The next section explains the proposed framework for gathering the recent trends in the Knowledge graph research field for the number of scientific articles found in this field and the major areas/regions/countries that contributed more to this field 67) .…”
Section: Knowledge Graphmentioning
confidence: 99%
“…Nowadays, machine learning and other approaches is widely utilized to solve a variety of difficult problems, such as making predictions and performing pattern recognition [5][6][7][8][9][10][11][12][13][14][15] . In modern era, there are others optimization techniques which is used in antenna structures like heuristic optimization techniques like genetic algorithms and particle swarm optimization [16][17][18][19][20] , but these algorithms examine for solution which is optimal by analyzing the output on individual data points and generating new and possibly improved search directions until a global maxima or minima is identified.…”
Section: Prerequisites For the Publicationmentioning
confidence: 99%
“…Robots are being created that can handle bulk harvesting with more accuracy and speed, allowing the fruit to reach your kitchen table faster. These kinds of tools boost the productivity and reduces the crop waste from the field 6) .…”
Section: Farm Harvesting Robotsmentioning
confidence: 99%